Transition readiness of adolescents to adult health care - Lara-Macaraeg, Beatrice Rodriguez; Cardinal, Avegail; Bermejo, Berith Grace (Frontiers in Pediatrics, 2023)
Background Transition in health care is a process wherein adolescents gradually prepare for and shift towards care in the adult system. An initial assessment of the readiness of these adolescents is fundamental in providing appropriate health services for them. This paper aims to determine the readiness of adolescent patients towards transitioning to adult care. Methods This is a prospective cross-sectional study utilizing an interviewer-guided modified Transition Readiness Assessment Questionnaire (TRAQ). Sixty-three adolescents ages 15 to 18 years seen in the Pediatric Outpatient Department (OPD) of a tertiary hospital in Baguio City from July 1 to October 31, 2020 were enrolled. Frequency and percentages were used to describe the demographic data; while mean score and standard deviation determined readiness based on a Likert scale. One-way ANOVA was utilized to determine association between factors and readiness to transition. Results For all domains of TRAQ, the mean score was 3.64, implying that they are not yet ready to transition. 49.2% belong to General Pediatrics. 44.4% belong to the Igorot ethnic groups. Most are still in High school, and majority of their parents finished High School level. Furthermore, the P-values were more than 0.05 for all variables suggesting no association between readiness to transition and the identified factors in this study. Discussion This study showed that adolescents who had both acute and chronic illnesses, were not yet ready to transition. Provision of a platform for assisting the adolescents in their assumption of bigger roles/responsibilities for their own health care is necessary to ensure proper transitioning to adult health care.